1) E = (3x - 5) (2x - 1) - 4 (x - 1)
E = 3x * 2x + 3x * (- 1) - 5 * 2x - 5 * (- 1) - 4 * x - 4 * (- 1)
E = 6x² - 3x - 10x + 5 - 4x + 4
E = 6x² - 17x + 9
2) a. Pour x = 0
E = 6x² - 17x + 9
E = 6 * 0² - 17 * 0 + 9
E = 6 * 0 + 9
E = 0 + 9
E = 9
b. Pour x = - 1
E = 6x² - 17x + 9
E = 6 * (- 1)² - 17 * (- 1) + 9
E = 6 * 1 + 17 + 9
E = 6 + 17 + 9
E = 32
c. Pour x = 1/2
x = 0,5
E = (3x - 5) (2x - 1) - 4 (x - 1)
E = (3 * 0,5 - 5) (2 * 0,5 - 1) - 4 (0,5 - 1)
E = (1,5 - 5) (1 - 1) - 4 (- 0,5)
E = - 4,5 * 0 - 2
E = - 2
d. Pour x = 2/3
E = 6x² - 17x + 9
E = 6 * (2/3)² - 17 * 2/3 + 9
E = 6 * 4/9 - 34/3 + 9
E = 24/9 - 34/3 + 9
E = - 26/3 + 9
E = 1/3